Educational Novelty And Its Relation With Visual Thinking With The Students Of Artistic Education Department (Al-Academy, 2018)
The two objectives of the current research are :-Uncover the views and opinions of the students of Artistic Education Department about the relation between educational novelty and its relation with visual . Identifying the capabilities of the students of artistic education department . The society of the research is the fourth class students of artistic education department - College of Fine Arts ( 83 students from both sexes ) . It was chosen ( 60 ) students sample of from both sexes by the researcher in order to conduct test upon them .The researcher has adopted descriptive methodology (correlation relationship ) and designed two tests , first dealing with educational novelty and the second deals with formal test of visual thinking .The instruments were subjected to procedures of honesty and fortitude . In order to show the results of the research which are reached by the researcher , statistical means are used as in the following :- ( T-Test ) , degree of severity and percentage weight , ( Pearson) correlation coefficient and (Cooper ) coefficient .The most important results reached by the researcher are :-Interaction of the students artistic education department with the components of educational novelty which gave positive indication for the importance of these novelty in educational process .